An Igbo Understanding of the Human Being: A Philosophical Approach - Ugwu, Anayochukwu Kingsley (Conatus - Journal of Philosophy, 2024)
The conception of the human being remains a philosophical controversial discourse among scholars to include Igbo extraction. The discourse has taken many dimensions describable as social, ontological, theologico-anthropological and even normative. Questions now follow: is the human being entirely a spiritual or physical being, or socio-political being, or even anhropological being? What differentiates his existence from the existence of other realities – be it physical or spiritual? It is in addressing these questions that this paper presents a socio-ontological conception of the human being held by Umuoka People which holds that the human being is Maadjvuru which interprets ‘Sustained-Survived/Surviving-Spirit.’ Doing this, the paper shall employ hermeneutical and phenomenological approaches to critically evaluate and undertake the discourse. The paper is expected to present more insights into the discourse by showing that the human being is a manifestation of the spirit, a concretized-spirit with complex physical and spiritual components whose existential experiences underpin his complex nature.